Grand Sulthan As The Basis For The Transfer Of Land Rights In Tebing Tinggi City : Study Of The Decision Of The Supreme Court No.1928k/Pdt/2021 - Munawan Syahputra; Hasdiana Juwita Bintang; Mochammad Erwin Radityo (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The transfer of land rights is a legal event/action that results in the transfer of rights from one legal subject to another legal subject, thereby causing the loss of authority over the land. Land transfer refers to the process or action that changes land ownership from one party to another. This can occur through a variety of means, including sale, inheritance, gift, or voluntary or forced surrender. For example, if someone sells a house to someone else, that is a transfer of land. This research includes normative legal research, so the legal materials used are primary, secondary and tertiary legal materials. The technique for collecting legal materials that will be used as a source in this research is library research, namely collecting legal materials by reading statutory regulations, official documents, journals, articles from the internet, and other literature that is closely related to The issues discussed are based on secondary legal materials. Transfer of land rights is a right to transfer land rights from an individual to a legal entity. Legal transitions usually occur due to legal acts and legal events. The implementation of the transfer of land rights can occur due to transfer or transfer. Switching, for example due to inheritance of Decision Number. 13/Pdt.G/2020/Pn Tbt The Panel of Judges rejected the Defendants' exception in its entirety in the main case, rejecting the plaintiff's claim in its entirety. Decision Number 422/Pdt/2020/PT Mdn that accepts the bandi application from the Comparator's Attorney for the original Plaintiff based on the Decision of the Tebing Tinggi District Court Number 13/Pdt.G/2020/Pn Tbt, dated 20 July 2020 which is appealed in the exception and rejects the exception Appellee 1 and Appellee II, in the main case, canceled the decision of the Tebing Tinggi District Court which was appealed. At the cassation level, Decision Number 1928 K/Pdt/2021, namely granting the cassation petition from the cassation applicants consisting of the Chair of the Community Empowerment Institution, formerly the Community Social Institution, represented by Iskandar and Lalang Village, Rambutan District, Tebing Tinggi City, represented by Lura Adi Supeno, thereby canceling the Medan High Court Decision Number 422/PDT/2020/PT Medan and dated 21 October 2020 which annulled the Decision of the Tebing Tinggi District Court Number 13/Pdt.G/2020/PN TBT dated 20 July 2020.